Serum anti-Müllerian hormone levels in euthyroid adolescent girls with Hashimoto's thyroiditis: relationship to antioxidant status. (August 2016) - Erol, Onur; Parlak, Mesut; Ellidağ, Hamit Yaşar; Parlak, Ayşe Eda; Derbent, Aysel Uysal; Eren, Esin; Yılmaz, Necat
Abstract: Objective: Free radical-mediated oxidative stress has been implicated in the etiopathogenesis of Hashimoto's thyroiditis (HT), which is the most common thyroid disorder in adolescents. HT requires lifelong thyroid surveillance, particularly in women of childbearing age to avoid adverse effects on reproductive function. The aims of this study were to investigate serum concentrations of anti-Müllerian hormone (AMH), a marker of ovarian reserve, in euthyroid adolescent girls with newly diagnosed HT and explore the relationships between AMH levels and biomarkers of antioxidant status. Study design: We recruited 57 non-obese (body mass index [BMI] Z -score < 2) adolescent girls with newly diagnosed HT and 50 age- and BMI-matched healthy controls for this case–control study. All participants were euthyroid. Hormonal and metabolic parameters, serum levels of AMH, and antioxidant status [paraoxonase (PON) and arylesterase (ARE) activities] were assessed. Results: Serum AMH levels were significantly higher and serum PON and ARE activities were significantly lower in adolescents with HT than in the controls ( p < 0.001 for all). No significant associations were detected between the AMH level and any of the clinical or biochemical parameters in the control group. Serum AMH levels were negatively correlated with PON ( r = −0.435, p = 0.001) and ARE ( r = −0.422, p = 0.001) activities in adolescents with HT. Conclusion: The AMH level was significantly higher while the PON and ARE activities were significantly lower in euthyroid adolescent girls with newly diagnosed HT.